A descriptive study of fatal drownings among children and adolescents in the United States, with a focus on retention pond deaths, 2004-2020. - Saroj Bista; Nichole L Michaels (PLOS Global Public Health)
The objective of this study was to characterize fatal drownings among children and adolescents, with a focus on retention pond drownings, and identify risk factors for these fatalities using child death review data. We acquired 2004-2020 National Fatality Review-Case Reporting System data for drowning deaths among youth 0-19 years. Retention pond drownings were identified through case narratives. We analyzed demographics, primary caregiver, supervisor, death investigation, and drowning-related variables across age groups (<1, 1-4, 5-9, 10-14, and 15-19 years) using either the Chi-square test or Fisher's Exact test, as appropriate, with a p-value of <0.05 indicating statistical significance. Of 7,539 drowning deaths reported during the study duration, 265 deaths occurred in retention ponds. Children 1-4 years comprised a greater proportion of retention pond drowning deaths (59.3%) compared to overall drowning deaths (50.9%) in this age group. In 51.3% of retention pond drowning deaths among children <5 years, supervision was needed but not provided. Most (80.4%) retention pond-related deaths among children <5 years and 50.7% of deaths among children 5-19 years were attributed to child neglect, poor or absent supervision, or exposure to hazards. Among all decedents who drowned in retention ponds, 19.1% were found to have a disability or chronic illness. Most retention ponds lacked local ordinances regulating water access (83.5%) and did not have barriers or protection (66.1%) or warning signs (82.0%). Younger children with poor or absent supervision who cannot swim are at high risk of drowning. Retention pond drownings are not infrequent, and most locations lack ordinances regulating water access or requiring barriers, such as fences. Greater efforts are needed to address this common hazard and environmental and policy strategies should be implemented to prevent future deaths.